Comparative virulence of Beauveria bassiana (Bals.) Vuill. and Metarhizium anisopliae (Metchnikoff) Sorokin to Spodoptera frugiperda (J.E. Smith) (Lepidoptera Noctuidae) - Montecalvo, Melissa P.; Navasero, Marcela M. (2021)
The invasive pest, fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae), was first reported to infest corn fields in the Philippines in 2019. In search for biological control agents against this pest, this study evaluated the bioefficacy of entomopathogenic fungi under laboratory conditions. The different life stages of S. frugiperda were exposed to Beauveria bassiana (Bals.) Vuill. and Metarhizium anisopliae (Metchnikoff) Sorokin. Larval hatch from treated eggs was reduced by the entomopathogenic fungi at 1 x 109 conidia/ml. Hatchability of treated eggs was significantly reduced in B. bassiana and M. anisopliae by 26.84% and 46.48%, respectively. Lethal infection to the larval instars (1st to 6th) ranged from 23.64 to 97.42% in B. bassiana and 23.13 to 61.33% in M. anisopliae at 10 days after treatment. B. bassiana was more virulent to 1st instar larvae, however, the two entomopathogenic fungi had similar degree of virulence to eggs, 2nd to 6th larval instars, prepupae, and pupae. Lower LC50 values were calculated for B. bassiana (0.0642 to 9.43 x 108 conidia/ml) than in M. anisopliae (1.61 x 106 to 6.13 x 109 conidia/ml). Mean time to larval mortality ranged from 4.59 to 7.46 days in B. bassiana and 4.06 to 7.79 days in M. anisopliae. However, the entomopathogenic fungi inflicted low mortality in treated prepupae and did not affect the pupal characteristics such as length, width, and weight. No significant difference was observed in the adult emergence of treated pupae. However, abnormalities in adults such as reduced size of wings and deformities were observed. These findings provided evidence on the effect of B. bassiana and M. anisopliae to the different life stages of S. frugiperda, hence, can be used as alternative to chemical insecticides against S. frugiperda.
Keywords: Agricultural pests; Corn disease and pest resistance; Biological pest control